Beneficial effect of rice bran extract against 3-nitropropionic acid induced experimental Huntington's disease in rats. (2015) - Kaur, Navneet; Jamwal, Sumit; Deshmukh, Rahul; Gauttam, Vinod; Kumar, Puneet
Graphical abstract: Abstract: Huntington's disease (HD) is a neurodegenerative disorder, characterized by progressive motor and non-motor dysfunction due to degeneration of medium spiny neurons in striatum. 3-Nitropropionic acid is commonly used to induce the animal model of HD. Rice bran is supposed to have beneficial effects on mitochondrial function. The present study has been designed to explore the effect of rice bran extract against 3-Nitropropionic acid induced neurotoxicity in rats. 3-Nitropropionic acid (10 mg/kg, i.p) was administered systemically for 21 days. Hexane and ethanol extract of rice bran were prepared using Soxhlation. Hexane (250 mg/kg) and ethanol extract (250 mg/kg) were administered per os for 21 days in 3-NP treated groups. Behavioral parameters (body weight, grip strength, motor coordination, locomotion) were conducted on 7th, 14th and 21st day. Animals were sacrificed on 22nd day for biochemical, mitochondrial dysfunction (Complex II), neuroinflammatory and neurochemical estimation in striatum. This study demonstrates significant alteration in behavioral parameters, oxidative burden (increased lipid peroxidation, nitrite concentration and decreased glutathione), mitochondrial function (decreased Complex II enzyme activity), pro-inflammatory mediators and neurochemical levels in 3-nitropropionic acid treated animals. Administration of hexane and ethanol extract prevented the behavioral, biochemical, neuroinflammatory (increased TNF-α, IL-1β and IL-6) and neurochemical alterations (decreased dopamine, norepinephrine, serotonin, 5-hydroxy indole acetic acid, GABA and increased 3, 4-dihydro phenyl acetaldehyde, homovanillic acid and glutamate levels) induced by 3-nitropropionic acid. The outcomes of present study suggest that rice bran extract is beneficial and might emerge as an adjuvant or prophylactic therapy for treatment of HD like symptoms.